Rezolvați ecuațiile :
X+X+X=6
3•x+4=2•X+11
2•(x+3)=6
Răspunsuri la întrebare
Răspuns de
3
X+X+X=6
3X=6
X=6:3
X=2
3•X+4=2•X+11
3X+4=2X+11
3X-2X=11-4
X=7
2(X+3)=6
2X+6=6
2X=6-6
2X=0
X=0:2X=0
Răspuns de
2
x+x+x=6
2x+x=6
3x=6
x=6:3
x=2
3x+4=2x+11
3x-2x=11-4
x=7
2*(x+3)=6
2x+2*3=6
2x+6=6
2x=6-6
2x=0
x=0
sau
2*(x+3)=6
x+3=6:2
x+3=3
x=3-3
x=0
2x+x=6
3x=6
x=6:3
x=2
3x+4=2x+11
3x-2x=11-4
x=7
2*(x+3)=6
2x+2*3=6
2x+6=6
2x=6-6
2x=0
x=0
sau
2*(x+3)=6
x+3=6:2
x+3=3
x=3-3
x=0
Alte întrebări interesante
Limba română,
9 ani în urmă
Limba română,
9 ani în urmă
Matematică,
9 ani în urmă
Limba română,
9 ani în urmă
Limba română,
9 ani în urmă
Limba română,
9 ani în urmă
Limba română,
9 ani în urmă